Efficacy of Medical Operations and Layout Planning Onboard Nontraditional US Navy Vessels at High Seas. (3rd September 2019) - Lindemann, E N S Cameron; Hoang, Tuan; Pierce, Eric; Franciose, Reginald; Pena, Mathew; Wilson, Tina; Bass, Cameron; Shattuck, Nita L; LaPorta, Anthony J
Abstract: Introduction: Attempting to expedite delivery of care to wounded war fighters, this study aimed to quantify the ability of medical and surgical teams to perform lifesaving damage control and resuscitation procedures aboard nontraditional US Navy Vessels on high seas. Specifically, it looked at the ability of the teams to perform procedures in shipboard operating and emergency rooms by analyzing motion of personnel during the procedures. Methods: One hundred and twelve damage control and resuscitation procedures were performed during a voyage of the US Naval Ship Brunswick in transit from Norfolk, Virginia, to San Diego, California. The ability of personnel to perform these procedures was quantified by the use of motion link analysis designed to track the movement of each participant as they completed their assigned tasks. Results: The link analysis showed no significant change in the number of movements of participants from the beginning to the end of the study. However, there was a learning effect observed during the study, with teams completing tasks faster at the end of the study than at the beginning. Conclusion: This shows that the working conditions aboard the US Naval Ship Brunswick were satisfactory for the assigned tasks, indicating that these medical operations may be feasible aboard nontraditional US Navy vessels.